33‐3: TADF Emitter Selection for Deep‐Blue Hyper‐Fluorescent OLEDs. Issue 1 (29th May 2019) - Baumann, Thomas; Budzynski, Matthias; Kasparek, Christian
Abstract : Blue fluorescent OLEDs are still the bottleneck for the power consumption in today's OLED panels. In recent years, the TADF technology has shown fast progress towards high‐efficiency deep‐blue emitter systems. The TADF technology can be used in a self‐emitting or in a co‐emitting (or hyper) approach. To make the co‐emitting system work efficiently, the combination of TADF and fluorescent emitter has to be chosen carefully. In this paper, we will discuss how to match TADF and fluorescent emitter combinations for the co‐emitting approach. We will also show results for highly efficient deep‐blue hyper‐fluorescent devices.